2010
DOI: 10.1007/s00125-010-1694-z
|View full text |Cite
|
Sign up to set email alerts
|

Oligodeoxynucleotide IMT504 induces a marked recovery in a streptozotocin-induced model of diabetes in rats: correlation with an early increase in the expression of nestin and neurogenin 3 progenitor cell markers

Abstract: Aims/hypothesis IMT504 is an oligonucleotide that promotes tissue repair in bone injury and neuropathic pain models by stimulating progenitor cells. Here we evaluated the effect of IMT504 on the recovery of islet function in a streptozotocin (STZ)-induced model of diabetes in the rat. Methods Male Sprague-Dawley rats were injected with STZ (60 mg/kg, i.p., day1) or citrate buffer (Control). Animals with glycaemia between 11 and 20 mmol/l on day 4 were injected with IMT504 (4 mg/animal in saline, s.c., STZ-IMT5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 11 publications
8
19
0
Order By: Relevance
“…IMT504 also promoted marked improvement in rat models of bone injury (22), neuropathic pain (7), and sepsis (5). Regarding diabetes, streptozotocin-induced toxic diabetes in rats was reversed by IMT504, improving glycemia, increasing islet number, ␤-cell content, ␤-cell proliferation, and early expression of pancreatic progenitor markers (3). Although IMT504 is active in rat and human cells, we have not yet demonstrated its effects in mice.…”
mentioning
confidence: 99%
“…IMT504 also promoted marked improvement in rat models of bone injury (22), neuropathic pain (7), and sepsis (5). Regarding diabetes, streptozotocin-induced toxic diabetes in rats was reversed by IMT504, improving glycemia, increasing islet number, ␤-cell content, ␤-cell proliferation, and early expression of pancreatic progenitor markers (3). Although IMT504 is active in rat and human cells, we have not yet demonstrated its effects in mice.…”
mentioning
confidence: 99%
“…5F), whereas Nes expression could not be determined. This may be due to the fact that nestin is expressed only during early development (74) or after islet damage (4,36,74). In addition, in adults, nestin-positive cells are found mainly in ductal and acinar cells (59,69,75), which would be scarce in our islet-rich samples.…”
Section: Islet Hormones and Transcription Factor Mrna Expression In Pmentioning
confidence: 85%
“…These effects include in vitro activation, proliferation, and expression of costimulatory molecules on B cells (Elías et al, 2003;Rodriguez et al, 2006a); immune modulatory effect on mice, rats, and primates when combined with a variety of antigens Montaner et al, 2011Montaner et al, , 2012Gan et al, 2009) Statistically significant differences as compared with control (0 mg/kg/day). *p < 0.05; **p < 0.02. improvement of tissue damage or disease in animal models (Rodriguez et al, 2006b;Hernando-Insúa et al, 2007;Coronel et al, 2008;Bianchi et al, 2010). All of these studies contributed to the dose selection for the present non-clinical studies.…”
Section: Pharmacological Effectmentioning
confidence: 97%
“…Also, IMT504, but not CpG ODNs, increases the number of adult mesenchymal stromal cells with multipotent differentiation capacity in vitro and in vivo (Hernando-Insúa et al, 2007). We have also found that treatment with IMT504 causes significant improvements in animal models of bone injury (Hernando-Insúa et al, 2007), neuropathic pain (Coronel et al, 2008), and type 1 diabetes (Bianchi et al, 2010). Furthermore, in human B cells from patients with chronic lymphocytic leukemia, IMT504 induces an immunogenic phenotype (up-regulation of CD25, CD40, CD80, and CD86 surface molecules) and stimulates apoptosis in vitro (Rodriguez et al, 2006b).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation